Proceedings of the 2017 ACM/IEEE International Conference on Human-Robot Interaction 2017
DOI: 10.1145/2909824.3020228
|View full text |Cite
|
Sign up to set email alerts
|

The When, Where, and How

Abstract: Adapting to users' intentions is a key requirement for autonomous robots in general, and in care settings in particular. In this paper, a comprehensive long-term study of a mobile robot providing information services to residents, visitors, and staff of a care home is presented, with a focus on adapting to the when and where the robot should be offering its services to best accommodate the users' needs. Rather than providing a fixed schedule, the presented system takes the opportunity of long-term deployment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They explicitly stated that the two heights tested were 188 cm, or the height of the badminton coach that the robotic avatar was representing, and 153 cm, or the average height of a Korean sixth-grade student. In contrast, although they do not report on the robot's height, the authors of [153] explained how their robot featured a touchscreen built to be height-accessible to walking and wheelchair-using participants alike. Finally, 19 studies [154][155][156] reported on participant handedness, albeit with no mention of ambidexterity; only one study [157] mentioned one ambidextrous participant.…”
Section: The Bodymentioning
confidence: 99%
“…They explicitly stated that the two heights tested were 188 cm, or the height of the badminton coach that the robotic avatar was representing, and 153 cm, or the average height of a Korean sixth-grade student. In contrast, although they do not report on the robot's height, the authors of [153] explained how their robot featured a touchscreen built to be height-accessible to walking and wheelchair-using participants alike. Finally, 19 studies [154][155][156] reported on participant handedness, albeit with no mention of ambidexterity; only one study [157] mentioned one ambidextrous participant.…”
Section: The Bodymentioning
confidence: 99%
“…We present the following interactive system as a case-study in this paper, to show how our proposed taxonomy can be used for a realworld use case. In this example case [31,32], an autonomous mobile robot has been deployed in a care home for a total of just over a year, in the context of the STRANDS project 1 . This experiment was split over three individual deployments, following an iterative design principle, spread over a duration of three years.…”
Section: Trust Loss As a Risk: A Case-studymentioning
confidence: 99%
“…Similarly, the robot can stimulate the user it accompanies to perform everyday activities [66]. Other functionalities are fall detection [67], meal assistance [68], or information and stimulation through messaging. In the aforementioned ALMI project, the TIAGo robot uses both its speech interaction for voice instructions and its object manipulation capabilities to help a user with mild motor and cognitive impairments prepare a meal.…”
Section: Expected Servicesmentioning
confidence: 99%